1999
DOI: 10.1111/1468-5949.00171
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Drawing in the UK and China

Abstract: We report the results of a comparative study of drawings completed by 952 children aged between 6-13 years in the UK and Chinese ordinary schools. Although there was no significant difference in standard between the drawings of these two cultural groups the drawings of 240 children who attended a week-end art school in Beijing were given consistently higher ratings. In addition, there were noticeable differences in style, composition, colour and depth cues among all three samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 2 publications
1
28
0
1
Order By: Relevance
“…Yet, a similar study that compared American and Chinese drawings of geometric shapes found that the two groups were rated similarly for creativity by both American and Chinese raters (Chen et al., 2002). There were no differences in rated artwork between Chinese and British school children, except for the higher ratings earned by Chinese children who attended a weekend art school (Cox, Perara, & Fan, 1998). Another study found that Japanese children produced higher rated drawings than British children (Cox, Koyasu, Hiranuma, & Perara, 2001).…”
mentioning
confidence: 81%
“…Yet, a similar study that compared American and Chinese drawings of geometric shapes found that the two groups were rated similarly for creativity by both American and Chinese raters (Chen et al., 2002). There were no differences in rated artwork between Chinese and British school children, except for the higher ratings earned by Chinese children who attended a weekend art school (Cox, Perara, & Fan, 1998). Another study found that Japanese children produced higher rated drawings than British children (Cox, Koyasu, Hiranuma, & Perara, 2001).…”
mentioning
confidence: 81%
“…The first was the third rater described above, and the second a 25-year old female researcher into children's drawings who holds an International Baccalaureate Certificate in Visual Arts. The mannequin drawings were rated using a modified version of the rating scale devised by Cox et al (1998). The criteria for clothing were omitted, as our mannequin had no clothes on.…”
Section: Scoring Of Drawingsmentioning
confidence: 99%
“…Davis (1991) also used adults with art experience (albeit more considerable than our raters) and cited evidence from her pilot work that there is greater reliability in ratings from this population. It should be noted, however, that there is a lack of evidence as to whether non-artists and artists differ in the rating of drawings generally (see Cox, Perara, & Xu, 1998).…”
Section: Scoring Of Drawingsmentioning
confidence: 99%